Molecular Dynamics Simulations of HEMA-Based Hydrogels for Ophthalmological Applications - Katarzyna Filipecka-Szymczyk; Malgorzata Makowska-Janusik; Wojciech Marczak (Molecules)
The structural and dynamic properties of poly(2-hydroxyethyl methacrylate) (PHEMA) and poly(N-vinylpyrrolidone-co-2-hydroxyethyl methacrylate) [P(VP-co-HEMA)], dry and as hydrogels, were studied by molecular dynamics simulations. The P(VP-co-HEMA) chains differed in the number of VP mers, distributed randomly or in blocks. In all considered configurations, HEMA and VP side chains proved relatively rigid and stable. Water concentration had a significant impact on their dynamic behavior. Oxygen atoms of hydroxyl and carbonyl groups of HEMA and carbonyl groups of VP are preferred sites of hydrogen bonding with water molecules. The copolymer swelling results in diffusion channels, larger in systems with high water content. In low-hydrated materials, water shows subdiffusion, while normal diffusion predominates in the high-hydrated ones. The VP side chains in copolymers with HEMA do not enhance the mobility of water.